2013
DOI: 10.6007/ijarems/v2-i4/121
|View full text |Cite
|
Sign up to set email alerts
|

The Dilemma of Success and Failure in Family Business: Overcoming Failure and Attaining Success

Abstract: The purpose of this study was to describe the present circumstances and setbacks of the family owned business in Pakistan. The current study has described the characteristics, types and the threats to the family business in Pakistan. This emphasizes on variables that differentiate successful family owned businesses from non successful family owned businesses. It also shed light on the mode of financing that are used by the family business and also on the succession plan that is adopted by the family business. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The success of any business depends upon its possession of knowledge resources, successful leveraging of these resources, and implementation of this knowledge in current processes and operations of the firm. The innovations, if given proper attention form managers and practitioners, can generate valuable outputs for organizations, helps them to be competitive, and ensure growth for a longer period (Qurashi et al, 2013). The present study is expected to be a valuable addition for managers and practitioners in SMEs sector.…”
Section: Findings Conclusion and Implicationsmentioning
confidence: 76%
“…The success of any business depends upon its possession of knowledge resources, successful leveraging of these resources, and implementation of this knowledge in current processes and operations of the firm. The innovations, if given proper attention form managers and practitioners, can generate valuable outputs for organizations, helps them to be competitive, and ensure growth for a longer period (Qurashi et al, 2013). The present study is expected to be a valuable addition for managers and practitioners in SMEs sector.…”
Section: Findings Conclusion and Implicationsmentioning
confidence: 76%
“…A few prior studies discussed potential reasons for the failure of family businesses. For instance, Qurashi et al. (2013) identified issues of succession planning, expectation, vision, and procedures as the main factors that determine the success and failure of family businesses, but overlooked entrepreneurial qualities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A few prior studies discussed potential reasons for the failure of family businesses. For instance, Qurashi et al (2013) identified issues of succession planning, expectation, vision, and procedures as the main factors that determine the success and failure of family businesses, but overlooked entrepreneurial qualities. Similarly, Zeeshan and Ali (2018) identified issues of succession planning, authority, and communication as the main reasons for the failure of family businesses.…”
Section: Sustainability Of Family Business In Pakistanmentioning
confidence: 99%